Implementation of ASN Professionalism Measurement Policy Based on the Regulation of the Minister of Administrative Reform Bureaucratic Reform Number 38 of 2018 concerning Measurement of the Professionalism Index of State Civil Apparatus in the Organizational Section of the Regional Secretariat of Semarang City - Muhammad Fakhri Rizqyanto; R. Slamet Santoso; Retna Hanani; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The purpose of this study was to describe the policy of measuring the professionalism of ASN in the Organizational Section of the Regional Secretariat of Semarang City and to analyze it based on Grindle's theory of policy implementation. This study used descriptive qualitative methods with data collection techniques including observation and interviews. The results of this study indicate that the implementation of the policy of measuring the professionalism of ASN in the Organizational Section of the Regional Secretariat of the City of Semarang has been carried out in accordance with the Regulation of the Minister of Administrative Reform Bureaucratic Reform Number 38 of 2018 concerning Measurement of the Professionalism Index of State Civil Apparatus in the dimensions of qualification, competence, performance, and discipline. As for the implementation of the measurement of the ASN professionalism index in the Organizational Section of the Regional Secretariat of the City of Semarang related to the influencing factors, according to Grindle Theory, it was found that the success of the implementation consisting of Content of Policy and Context of Policy in each indicator had a positive effect.